MOLECULAR CHARACTERIZATION OF CONTAGIOUS CAPRINE PLEUROPNEUMONIA (CC PP) I N SMALL RUMINANTS OF KHYBER PAKHTUNKHWA, PAKISTAN - U. Sadique; Z. I. Chaudhry; M. Younas; A. A. Anjum; Z. U. Hassan; M. Idrees; M. Mushtaq; A. Sajid; S. M. Sabtain (Journal of Animal and Plant Sciences, 2012)
This study was conducted to determine the molecular identification of Contagious Caprine Pleuropneumonia in field outbreak. The study included isolation and identification of Mycoplasma species from field outbreaks by usage of a selective differentiating hay flick medium, growth inhibition test and a Polymerase Chain Reaction (PCR) test. Out of 120 inoculated samples, 30% and 22.5% were positive on culture from lungs and pleura. Isolates were identified as Mycoplasma mycoides subspecies Capri by a growth inhibition test and PCR. Similarly, tissue samples that were negative on culture were also subjected to PCR analysis. Out of 120 samples 62.5% and 54.16% from lungs and pleura, respectively, were positive. On statistical analysis, a significant difference (P<0.05) was found between results of PCR and culture. This difference reflects that the PCR technique is more sensitive than the culture method. Based upon these findings, disease was prevalent in almost all selected regions of province associated with Mycoplasma mycoides subspecies Capri.
Keywords: Contagious Caprine pleuropneumonia; growth inhibition test; PCR; Mycoplasma mycoides capri; goat